2020
DOI: 10.1177/0954405420937558
|View full text |Cite
|
Sign up to set email alerts
|

Extended model for selection of optimum turning conditions based on minimum energy considerations

Abstract: Reducing energy consumption in manufacturing is essential for using energy effectively and minimising carbon footprint. In this study, the equation for selecting optimum cutting conditions to minimise energy footprint was extended by considering the fact that as tool wear increases, power and specific energy also increase. This new model enables selecting optimum conditions for energy-smart machining by considering energy footprint, cutting tool utilisation and the volume of material to be removed. This timely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…1 Therefore, energy conservation in manufacturing has become a critical issue and must be addressed to improve economic benefits and minimise environmental impacts. 2,3…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Therefore, energy conservation in manufacturing has become a critical issue and must be addressed to improve economic benefits and minimise environmental impacts. 2,3…”
Section: Introductionmentioning
confidence: 99%
“…1 Therefore, energy conservation in manufacturing has become a critical issue and must be addressed to improve economic benefits and minimise environmental impacts. 2,3 Laser processing has become an increasingly indispensable part of competitive manufacturing throughout the world. 4 In particular, laser welding has attracted considerable attention in the automotive, aerospace, nuclear, medicine and petrochemical industries.…”
Section: Introductionmentioning
confidence: 99%
“…To decrease environmental impacts and obtain sustainable manufacturing, the energy consumed and carbon emissions should be minimized for the rotary turning operation. 21,22 The empirical models of the average roughness, turning forces, and cutting temperature for various ADRT processes have been proposed in the previous publications. Unfortunately, the comprehensive models of the total specific energy and carbon emission have not been developed.…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of the blunt and edge of the micro-textured tool on the MF and MT in the milling titanium alloy have been explored by Tong et al (2020) [11], in which the optimal geometric characteristic was selected using the support vector regression and genetic algorithm; and the authors stated that the enhancements in the tool life (TL) and SR were 33% and 26%, respectively with the aid of the optimal micro-textured tool. Alswat et al (2020) proposed a new energy model to identify optimal values for machining parameters of turning operations, taking into account the energy footprint, the cutting tool utilization and the material removed volume [12], in which a case study was employed to validate the effectiveness of the proposed approach; and the results showed that the proposed model was effectively applied to generate reliable machining parameters, as compared to traditional ones.…”
Section: Introductionmentioning
confidence: 99%
“…The authors stated that the enhancements in the tool life (TL) and SR were 33% and 26%, respectively with the aid of the optimal micro-textured tool. Alswat and Mativenga 12 proposed a new energy model to identify optimal values for machining parameters of turning operations, taking into account the energy footprint, the cutting tool utilization and the material removed volume, in which a case study was employed to validate the effectiveness of the proposed approach. The results showed that the proposed model was effectively applied to generate reliable machining parameters, as compared to traditional ones.…”
Section: Introductionmentioning
confidence: 99%